Pengaruh Ukuran Dewan Komisaris, Komite Audit dan Kepemilikan Manajerial Terhadap Kinerja Perusahaan: Studi pada Perusahaan Sektor Energi dan Pertambangan yang Terdaftar di Bei 2021-2024 - Dini Nur Seha; Indianik Aminah; Fatimah (IAI Nasional Laa Roiba Bogor, 2025)
In the current reality, the performance of companies in the energy and mining sectors does not always show a consistently improving trend, even though government support and abundant resource potential are already available. The purpose of this study is to determine the effect of the board of commissioners' size, audit committee, and managerial ownership on company performance in energy and mining sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. This study uses a quantitative descriptive approach with a sample consisting of 18 energy and mining sector companies. Data were obtained from the financial reports of energy and mining sector companies on the IDX for the years 2021–2024 through the official IDX website (www.idx.ac.id) and related web sources. The author also conducted a literature review from journals, books, and previous relevant research. The results of this study indicate that the size of the board of commissioners has no effect on the performance of energy and mining sector companies listed on the IDX in 2021–2024. The audit committee has an effect on company performance, while managerial ownership has no effect. Simultaneously, it was found that the size of the board of commissioners, the audit committee, and managerial ownership collectively influence the performance of energy and mining sector companies on the IDX during 2021–2024, as the three complement each other in corporate governance.